Comparison of the Diagnostic Yield of EUS Needles for Liver Biopsy: Ex Vivo Study. (13th September 2017) - Lee, Woo Jung; Uradomo, Lance T.; Zhang, Yang; Twaddell, William; Darwin, Peter
Abstract : Background and Aims. EUS-guided liver biopsy is an emerging method of liver tissue acquisition which is safe and had been shown to produce excellent histological yield. There is limited data comparing the diagnostic yield of different FNA needles. We aimed to compare the diagnostic performance of four commercially available 19-gauge FNA needles. Methods . Four FNA needles and one percutaneous needle were used to perform liver biopsies on two human cadaveric livers: Cook Echotip Procore™, Olympus EZ Shot 2™, Boston Scientific Expect Slimline™, Covidien SharkCore™, and an 18-gauge percutaneous needle (TruCore™, Argon Medical Devices). Each needle obtained biopsies by three, six, and nine complete back-and-forth motions of the needle ("throw") with a fanning technique. The combined lengths of specimen fragments and the total number of complete portal tracts (CPT) were measured by a blinded pathologist. One-way analysis of variance (ANOVA) and Bonferroni correction were used for statistical analysis. Results. A total of 52 liver biopsies were performed. The Covidien SharkCore needle had significantly greater number of CPT compared to other FNA needles. The number of "throws" did not impact the number of CPT significantly. There was no statistically significant difference in mean total specimen length between each FNA needle type. Conclusion . The Covidien SharkCore needle produced superior histological specimen by capturing more CPT, possibly due to its unique needle design.